Assistance in Utilization of Plastic Waste through Eco-Paving Blocks at Adiwiyata Elementary School, Demak Regency - Aan Widiyono; Yayan Adi Saputro; Fivin Bagus Septiya Pambudi; Ahmad Bagus Bambang Heri Hermawan; Much Ardian Mahardika (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Plastic waste is the main problem of environmental pollution at SDN Gebang 1, an Adiwiyata school in Demak Regency. Piles of plastic waste need to be appropriately managed because they need to create a better impression of the vision and mission of the Adiwiyata School. Another problem was seen during the rainy season when plastic waste blocked the water flow. SDN Gebang 1 experienced flooding until the water entered the classrooms. One of the efforts made by the school is through collaboration with OISCA to make it a green school. However, schools still need help with waste handling in the school area. The program aims to utilize waste through Eco-Paving Blocks. The community service method includes five stages: socialization, training, application of technology, mentoring, and monitoring. The activities obtained results from using plastic waste in the elementary school environment, which was 100% because partners agreed that plastic waste must be managed well. Applying the TTG Eco-Paving Block tool is easy to use, with results of 85.25%. The successful implementation of the activity received a score of 90.50%. Partners can utilize 87.50% of plastic waste through the TTG Eco-Paving Block tool. The implementation of practical activities by teachers obtained results of 92.25%. Thus, teachers need assistance utilizing plastic waste through the TTG Eco-Paving Block tool, which helps reduce plastic waste at SDN Gebang 1.